Penerapan Developmental Peer Appraisal untuk Meningkatkan Kohesivitas Tugas - Ermy Herawati; Fathul Himam (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This study aimed to examine the effect of the application of developmental peer appraisals to increase the cohesiveness tasks among team members. This research was implemented a quasi experimental design with untreated control group design with pretest and posttest. The research subjects were ‘Waroeng SS’ workers consisted of 30 persons. Subjects were divided into two groups: experimental group and control group where each group consisted of 15 persons. The experimental group was given the treatment of the application of developmental peer appraisal. Two weeks after being given treatment, task cohesiveness was measure by using modified task cohesiveness scale compiled by Beaubien and Carless and De Paola consisting of nine item. Analysis of data was using a nonparametric test of Mann-Whitney. The study showed that task cohesiveness did not increase significantly after implementation of developmental peer appraisal (Z=-1.222, p> 0.05). This result were discussed further.